Satisfaction in concepts of the organisation’s intangible assets and the processes of production preparation - Winkler, Renata; Łukasik, Paweł (Satysfakcja w koncepcjach zasobów niematerialnych organizacji a procesy przygotowania produkcji, 2019)
This article addresses the issue of employees’ job satisfaction in terms of the intangible assets of an organisation and simultaneously indicates the role which both of those aspects play in implementing the production preparation process. Through the use of a systematic literature review method, it was possible to identify research studies devoted to the position of satisfaction in the concepts of intangible assets and intellectual capital, and the study results in terms of relations between various intangible assets, such as the company’s reputation or structural capital, and job satisfaction. The conclusions of this study are particularly important for production preparation. They indicate how important the reputation of the company and other intangible assets are for employees’ satisfaction and for retaining them in the company, which is crucial for the implementation of technologically advanced research and development
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 2, s. 41-48
Keywords: job satisfaction; intangible assets; processes of production preparation; zadowolenie z pracy; wartości niematerialne; procesy przygotowania produkcji